A Silurian short-great-appendage arthropod - Siveter,DJ; Briggs,DEG; Siveter,DJ; Sutton,MD; Legg,D; Joomun,S (Proceedings of the Royal Society B: Biological Sciences, 2014)
A new arthropod, Enalikter aphson gen. et sp. nov., is described from the Silurian (Wenlock Series) Herefordshire Lagerstätte of the UK. It belongs to the Megacheira (=short-great-appendage group), which is recognized here, for the first time, in strata younger than mid-Cambrian age. Discovery of this new Silurian taxon allows us to identify a Devonian megacheiran representative, Bundenbachiellus giganteus from the Hunsrück Slate of Germany. The phylogenetic position of megacheirans is controversial: they have been interpreted as stem chelicerates, or stem euarthropods, but when Enalikter and Bundenbachiellus are added to the most comprehensive morphological database available, a stem euarthropod position is supported. Enalikter represents the only fully three-dimensionally preserved stem-group euarthropod, it falls in the sister clade to the crown-group euarthropods, and it provides new insights surrounding the origin and early evolution of the euarthropods. Recognition of Enalikter and Bundenbachiellus as megacheirans indicates that this major arthropod group survived for nearly 100 Myr beyond the mid-Cambrian.